The Validity and Reliability of the Theory Behind BIM Adoption in The Facility Management Using PLS-SEM - Abd Wahab, Siti Rashidah Hanum; Mohd Sahri, Nurul Nabila; Muhammad, Faudzi; binti Abdul Hadi, Nurulhudaya; Ismail, Balkhiz; Nizam Akbar, Anis Rosniza (Online Journal for TVET Practitioners, 2023)
The usage of Building Information Modelling (BIM) in the Facility Management (FM) sector will significantly speed up the design and construction phases. However, most facility managers continue to use the traditional paper-based approach to manage facility maintenance and operations, which includes designs and spreadsheets. The goal of this research is to pinpoint the factors that affect BIM’s acceptability in the FM sector. Six factors, including organisational culture, individual competency, perceived usability, perceived ease of use, individual intention, and organisational aim in the context of facilities management services, were found. Prior to that, it is necessary to determine whether the theory supporting the adoption of BIM in facility management is valid and reliable. This study used an abductive methodology that blends qualitative and quantitative techniques. 30 respondents completed a set of questionnaires as part of the study’s pilot test. Based on the findings of the pilot study, it can be demonstrated that the high degree of Cronbach’s Alpha values is accepted, demonstrating the validity and reliability of the theory supporting the adoption of BIM in facility management and its high degree of internal consistency. This study demonstrates that there are important factors that affect how well BIM is received in the facilities management sector. All the six factors have a significant impact indicating that the theory underlying the adoption of BIM in facility management is valid and reliable and has a high degree of internal consistency.